2018
DOI: 10.1038/s41598-018-25004-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of the HIV Epidemic in Three German Metropolitan Regions – Cologne/Bonn, Munich and Hannover, 1999–2016

Abstract: Using HIV sequence data to characterize clusters of HIV transmission may provide insight into the epidemic. Phylogenetic and network analyses were performed to infer putative relationships between HIV-1 partial pol sequences from 2,774 individuals receiving care in three German regions between 1999–2016. The regions have in common that they host some of the largest annual festivals in Europe (Carnival and Oktoberfest). Putative links with sequences (n = 150,396) from the Los Alamos HIV Sequence database were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…The prevalence of CRF01_AE and subtype B decreased by around 20% (from 91.9 to 73.6%) between 2008 and 2016, whereas that of CRF07_BC and other CRFs or URFs increased. The few network studies that have been carried out in areas with multiple HIV subtypes and have typically used one single genetic threshold (Hoenigl et al, 2016a;Stecher et al, 2018). Rates of HIV-1 evolution vary across subtypes (Patino-Galindo and Gonzalez-Candelas, 2017;Bbosa et al, 2019a), and no previous studies have focused on HIV evolution or threshold selection for our local epidemic strains.…”
Section: Threshold Selection In An Area With Multiple Hiv-1 Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of CRF01_AE and subtype B decreased by around 20% (from 91.9 to 73.6%) between 2008 and 2016, whereas that of CRF07_BC and other CRFs or URFs increased. The few network studies that have been carried out in areas with multiple HIV subtypes and have typically used one single genetic threshold (Hoenigl et al, 2016a;Stecher et al, 2018). Rates of HIV-1 evolution vary across subtypes (Patino-Galindo and Gonzalez-Candelas, 2017;Bbosa et al, 2019a), and no previous studies have focused on HIV evolution or threshold selection for our local epidemic strains.…”
Section: Threshold Selection In An Area With Multiple Hiv-1 Subtypesmentioning
confidence: 99%
“…HIV molecular networks can be used not only to guide targeted intervention in key subpopulations (Aldous et al, 2012;Lubelchek et al, 2015;Castley et al, 2017;Chaillon et al, 2017;Zhang et al, 2017;Stecher et al, 2018;Volz et al, 2018;Ragonnet-Cronin et al, 2019;Board et al, 2020), but also to reconstruct the history of HIV spread between populations (Kouyos et al, 2010;Brenner et al, 2017;Pineda-Pena et al, 2018;Delgado et al, 2019;Fabeni et al, 2019). Several local and national studies conducted in recent years have monitored the dynamics of HIV molecular clusters and evaluated their expansion speed (Chan et al, 2015;Mehta et al, 2018;Ragonnet-Cronin et al, 2018;Wertheim et al, 2018;Jovanovic et al, 2019;Dennis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sexual behaviors, condom use, male circumcision, antiretroviral therapy and sharing syringes among drug users all have different impacts on HIV/AIDS prevalence (Zhang et al, 2008;Nikolopoulos and Bonovas, 2017;Kelly et al 2017). A series of studies on HIV/AIDS prevalence in the United States (Rios-Gonzalez and Flores-Enriquez, 2018), China (Yuan et al, 2018;Yang et al, 2017;Lu et al, 2017;Tang et al, 2016;Pan et al, 2016), Africa (Scriven et al, 2016), Germany (Stecher et al, 2018) and Ukraine (Vasylyeva et al, 2018) have been published, but rare national studies were reported about the impacts of regional and age differences on clinical epidemiology of HIV/AIDS. Considerable changes of related policies have been provided including the implementation of innovative strategies and a comprehensive anti-HIV program over the last 20 years in China.…”
Section: Introductionmentioning
confidence: 99%
“…Despite declining numbers of incident infections, HIV continues to have a disproportionate impact on men who have sex with men (MSM). [1][2][3] The efficacy of tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) for HIV pre-exposure prophylaxis (PrEP) in MSM has been well documented in several randomized controlled trials. [4][5][6] The effectiveness of TDF/FTC for HIV PrEP strongly depends on adherence.…”
Section: Introductionmentioning
confidence: 99%